Effectiveness of Differentiated Learning Materials Oriented toward Nature of Science to Improve Scientific Literacy Skills - Hanifa Rachmah Kamila; Sari Edi Cahyaningrum; I Gusti Made Sanjaya (Jurnal Penelitian Pendidikan IPA, 2023)
This research aimed to describe the effectiveness of differentiated learning materials oriented toward the nature of science (NoS) to improve students’ scientific literacy skills. The research type is quasi-experiment with one group pretest-posttest design. The research was given to 31 students in VIII-A class of Junior High School 16 Gresik. The effectiveness of differentiated learning materials oriented toward the nature of science (NoS) was obtained from the scientific literacy skills test and student response questionnaire. The student’s scientific literacy skills test showed an improvement in gain score between the pretest and posttest scores of 0.64, which is in the medium category; besides that, most students gave positive responses to the learning materials seen from the percentage of interest in learning materials 84.68% (very interested). The data obtained showed that differentiated learning materials oriented toward the nature of science were effective as learning materials to improve students’ scientific literacy skills in Merdeka Curriculum